Detection of bacterial samples on the aquatic ecosystems adjacent to Saquarema Lagoon – Rio de Janeiro - Nogueira, Barbara Araujo; Olivella, Julianna Giordano Botelho; Gil, Adriana Costa; Meirelles-Pereira, Frederico; Gonçalves, Verônica Dias; Andrade, Arnaldo Feitosa Braga de; Bello, Alexandre Ribeiro; Pereira, José Augusto Adler (Revista de Ciências Médicas e Biológicas, 2015)
Introduction: Saquarema Lagoon (RJ) has a high ecological and economic value owing to its multiple uses. The population’s constant growth increases the amount of sewage containing bacteria and antimicrobial drugs that are discharged to the environment. Objectives: to detect Gram negative bacilli able to colonize or infect humans and animals and determine their antimicrobial resistance profiles. Methodology:samples were collected in the city centre in April 2010 and at Jaconé (Lagoon’s most preserved site) in February 2011. The total and thermo tolerant coliforms were determined and the isolation of samples was made using agar media containing 32cg/ mL of cephalotin. All samples were tested for antimicrobial susceptibility (AST) and on 16 samples, plasmid DNA was extracted. Results: different Gram negative bacteria were detected, such as: Enterobacter spp, Citrobacter freundii, Klebsiella pneumoniae and Pseudomonas aeruginosa. The coliform results showed that the water quality is proper for Human recreation. AST results demonstrated the existence of bacteria resistant to antimicrobial drugs frequently used in the community. It was possible to detected high molecular weight plasmids and nine samples (56,25%) showed at least one plasmid DNA electrophoresis band. Conclusions: there were not detected resistant samples to antimicrobial drugs normally used in hospital settings, which may possibly refute the idea of a contamination by nosocomial and/or veterinary sewage discharge.